The Impact of COVID-19 on International Arbitration - Kamwengo, Mary (Department of Commercial Law, 2023)
On 11 March 2020, the World Health Organization categorised the global outbreak of COVID-19 as a pandemic and implored countries to take effective and immediate measures to prevent it from spreading further. Nationwide lockdowns, travel restrictions and physical distancing measures were subsequently effected in several countries, causing many businesses to close down. In turn, many courts found themselves limiting their operations and postponing most hearings save for urgent matters. Whilst different courts were functioning at limited capacity and litigants were struggling to figure out how to make changes to their procedural timetables and deal with the uncertainties brought on by the pandemic, major arbitral institutions intimated their intention to proceed with new and ongoing disputes. The position adopted by these institutions can be attributed to the inherent flexibility and consensual nature of the international arbitration dispute resolution process. Being a consensual and flexible process, international arbitration is well placed to allow cases to advance amidst the pandemic as its procedures can easily be tailored to meet the needs of disputing parties who may be across various jurisdictions. Despite its flexibility, international arbitration has not been impervious to the disruption which has been occasioned by the COVID19 pandemic.